Mengoptimalkan Pendidikan dengan Sumber Daya Terbatas: Tantangan Mengajar di Sekolah Dasar - Kurnia; Utami, Cecilia Putri; Hikmah, Khoirunnisa Durotul; Kaharap, Joni Tito; Setiawan, Heri; Agustiani, Reni (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This study explores the contribution of a community service team in the education sector through the Community-Based Learning Program (KKN) at SD Negeri 3 Tampa, East Barito, Indonesia. The program aimed to enhance students’ focus, motivation, and English language proficiency in response to ongoing challenges, including a shortage of qualified educators and limited learning resources. Adopting a social approach, the implementation involved systematic observation, problem identification, strategic planning, and execution by students from the University of Palangka Raya. The results indicate a significant improvement in students’ motivation and English skills, particularly in speaking and comprehension. Key program components included English teacher assistance, innovative learning methods, and motivation and awareness enhancement. Feedback from both students and teachers highlighted increased student engagement and positive learning outcomes. Despite these achievements, sustained development efforts and institutional support remain essential to ensure long-term impact.